The impact of online celebrity in livestreaming E-commerce on purchase intention from the perspective of emotional contagion. (November 2021) - Meng, Lu (Monroe); Duan, Shen; Zhao, Yijun; Lü, Kevin; Chen, Siyun
Abstract: The purpose of this study is to investigate (1) if online celebrities can directly emotionally influence consumers, and (2) if the other audiences of the same livestream can indirectly emotionally influence consumers to increase their willingness to buy the products recommended by the online celebrities. Therefore, to understand the reasons for the successes of livestreaming e-commerce. Two studies have been conducted: in Study 1, a questionnaire-based survey has been used for data collection and AMOS version 17.0 software was used to analyze the data of the Structural Equation Modelling (SEM); in Study 2, a web data crawler for data collection was developed using python software, and the collected data were processed by ICTCLAS text splitting tool and analyzed by Stata/MP 13.0 software for the econometric model constructed in this paper. This study found that the performance of online celebrities can stimulate consumers' emotions, and thus enhance consumers' purchase intention regarding the products recommended. This study also found that pleasure, arousal, admiration, and emotional trust can influence purchase behavior for cosmetics and clothing. For food products, only pleasure emotion, arousal emotion and admiration emotion can increase the willingness to purchase such products. For other audiences who watch the same Online celebrity for food products, the pleasure, arousal, and admiration emotions can increase searches for, and purchases of the products recommended. This study identified that online celebrities' performances can emotionally influence consumers' willingness to purchase products recommended by online celebrities directly. In addition, the emotions of audiences watching the online celebrities can indirectly influence consumers' willingness to purchase products recommended by the online celebrities. Graphical abstract: Image 1